The Melanin-Concentrating Hormone (MCH) System: A Tale of Two Peptides - Diniz, Giovanne B.; Bittencourt, Jackson C. (Frontiers in Neuroscience, 2019)
The melanin-concentrating hormone (MCH) system is a robust integrator of exogenous and endogenous information, modulating arousal and energy balance in mammals. Its predominant function in teleosts, however, is to concentrate melanin in the scales, contributing to the adaptive color change observed in several teleost species. These contrasting functions resulted from a gene duplication that occurred after the teleost divergence, which resulted in the generation of two MCH-coding genes in this clade, which acquired distinctive sequences, distribution, and functions, examined in detail here. We also describe the distribution of MCH immunoreactivity and gene expression in a large number of species, in an attempt to identify its core elements. While initially originated as a periventricular peptide, with an intimate relationship with the third ventricle, multiple events of lateral migration occurred during evolution, making the ventrolateral and dorsolateral hypothalamus the predominant sites of MCH in teleosts and mammals, respectively. Substantial differences between species can be identified, likely reflecting differences in habitat and behavior. This observation aligns well with the idea that MCH is a major integrator of internal and external information, ensuring an appropriate response to ensure the organism homeostasis. New studies on the MCH system in species that have not yet been investigated will help us understand more precisely how these habitat changes are connected to the hypothalamic neurochemical circuits, paving the way to new intervention strategies that may be used with pharmacological purposes.